A Study of Port Facilities in Supporting Throughput at Sunda Kelapa Port - Syifa Fajar Maulani; Wenny Ananda Larasati; Melia Handayani; Muhammad Rizky; Nina Evriliyani; Shoimah Annisa Ramadhani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Sunda Kelapa Port is a collector port that plays an important role in inter-island goods distribution, yet it still faces facility limitations and low operational efficiency. Although the number of loading and unloading activities increases each month, the predominantly manual operational processes indicate the need for facility modernization. This study aims to analyze the condition of facilities at Sunda Kelapa Port and evaluate throughput values to determine their relationship with port performance. A qualitative descriptive method was employed through an assessment of primary and functional port facilities as well as throughput calculations based on loading and unloading data from August to October 2025. This analysis was conducted to assess the capacity of the existing facilities to support increased cargo flow. The results show that the 54 percent decrease in general cargo throughput in September, followed by a limited increase in October, was influenced by inadequate conditions of the public pier, storage yard, and warehouse. For container cargo, the significant 90 percent decline in throughput was caused by the limited capacity of the container yard, insufficient stuffing– stripping areas, and the absence of modern container-handling equipment. Overall, the study concludes that the existing facilities at Sunda Kelapa Port are not yet optimal in supporting throughput growth. Modernizing port facilities is essential to improve efficiency and strengthen the port’s role within the national logistics system.